Wording Robotics Discourses and Representations on Robotics - Laumond, Jean-Paul.; Danblon, Emmanuelle; Pieters, Céline; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Robots challenge humans' beliefs and expectations. Hence, regardless of whether they are the audience of a conference, the visitors of a lab, the citizens in general, some journalists, or the European Parliament, the first step in order to gain a better understanding of the field of robotics is obviously to consult the experts. Roboticists seem indeed to be in the best position to guide society in this matter, whether it is in the everyday life or within an official institution. Today however, there is a gap between the robots, as they are actually thought and built, and the intelligent and autonomous machines, as they are perceived by the society. How can we explain it? Do the words borrowed from the living organisms and used to describe robots play a role in the confusion about the status of the discipline of robotics? The texts gathered within this book focus on the problematic of wording robotics from various perspectives. They are the resultsof a unique interdisciplinary meeting gathering roboticists, linguists, philosophers and neuroscientists, the 4th Workshop of Anthropomorphic Motion Factory held at LAAS-CNRS in Toulouse on Nov 31st - Dec 1st 2017.
Embodied language in brains and robots: the question of geometrical reference frames -- The multiple ways of expressing "intelligence" -- The stochastic intelligence. A technical model from ancient Greece to robotics -- Metaphor, Metonymy, and Personification in the Language of Robotics -- Artificial moral agents. Really? -- The Language of the Possible -- Beyond the conflict between "Touch" and "Feel" in robotics -- Speaking about robots: languages and characterizations -- Visitor or Artefact ! An experiment with a humanoid robot at the Musée du Quai Branly in Paris -- Adopting the intentional stance towards humanoid robots -- ChatBot the Robot. A philosophical drama in four questions and five acts.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Psycholinguistics; Control, Robotics, Automation; Artificial Intelligence; Psycholinguistics and Cognitive Lingusitics